Application of Ranked Set Sampling to Normality Tests - Erem, A.; Arslan, G. (Journal of Advances in Applied & Computational Mathematics, 2015)
The normality assumption is used in many statistical analyses and is also a fundamental concept in statistics. Because of this there are many statistical tests for testing the normality assumption. Two of the most primitive ones are the R and Z tests. The main aim of this study is to investigate the application of ranked set sampling to these tests. Therefore, by using the idea of ranked set sampling, modifications of the R and Z tests are considered. Using simulations the results of these new tests are discussed.